HUBUNGAN ANTARA KASIH SAYANG DAN PERHATIAN TERHADAP KEPERCAYAAN DIRI REMAJA YANG TINGGAL DI PANI ASUHAN PUTRI AL-KAZEM ACEH BESAR - Rusli Yusuf; Ruslan Ruslan; Ati Winarni (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
The purpose of article writing to determine the significant relationship between affection and attention to the confidence of adolescents living in the Al-Kazem Aceh Besar Orphanage. This research uses correlation method with quantitative approach. Data collection techniques used ques- tionnaires. While the sampling technique using total sampling. The total sampling technique in the study was all female teenagers living at the Al-Kazem Aceh Besar Orphanage, which amounted to 34 people, especially young women aged 11-17 years. The results of study show (1) The correlation coefficient between affection and adolescent self-confidence showed a fairly strong correlation level, (2) the correlation coefficient between attention and confidence showed strong relation rate, and (3) coefficient The correlation between affection and attention with adolescent self-confidence shows a fairly strong.